Sleep Disorder and Long-Term Mortality Among Sepsis Survivors: A Nationwide Cohort Study in South Korea - Song, In-Ae (Nat Sci Sleep, 2021)
BACKGROUND: We aimed to investigate the association of sleep disorder diagnosis among sepsis survivors with 5-year all-cause mortality. METHODS: Using the National Health Insurance Service (NHIS) database of South Korea, we included adult sepsis survivors who were primarily diagnosed with sepsis between 2011 and 2014 and survived for more than one year after diagnosis. The diagnosis of sleep disorders was evaluated using the International Classification of Diseases, 10th revision codes of G47* in the NHIS database. RESULTS: In total, 45,826 survivors of sepsis were included in this analysis. Among the sepsis survivors, 2935 (6.4%) were newly diagnosed with a sleep disorder within 1 year after the date of sepsis diagnosis, while 7938 (17.3%) were already diagnosed with sleep disorder before the date of sepsis diagnosis. In the multivariable Cox regression, the risk of 5-year all-cause mortality in the pre- and post-sepsis sleep disorder groups was 1.19-fold (hazard ratio: 1.19, 95% confidence interval: 1.14–1.24; P<0.001) and 1.79-fold (hazard ratio: 1.79, 95% confidence interval: 1.70–1.89; P<0.001) higher than that of the control group. CONCLUSION: A 6.4% of sepsis survivors in South Korea were newly diagnosed with a sleep disorder within 1 year of sepsis diagnosis. Although both pre- and post-sepsis sleep disorders were associated with a higher 5-year all-cause mortality rate, the risk of the 5-year all-cause mortality in the post-sepsis sleep disorder group was higher than that in the pre-sepsis sleep disorder group.